2024
DOI: 10.3389/fimmu.2024.1332939
|View full text |Cite
|
Sign up to set email alerts
|

The next-generation DNA vaccine platforms and delivery systems: advances, challenges and prospects

Bowen Lu,
Jing Ming Lim,
Boyue Yu
et al.

Abstract: Vaccines have proven effective in the treatment and prevention of numerous diseases. However, traditional attenuated and inactivated vaccines suffer from certain drawbacks such as complex preparation, limited efficacy, potential risks and others. These limitations restrict their widespread use, especially in the face of an increasingly diverse range of diseases. With the ongoing advancements in genetic engineering vaccines, DNA vaccines have emerged as a highly promising approach in the treatment of both genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 239 publications
0
4
0
Order By: Relevance
“…Genome insertion could be controlled with modified DNA sequences and their low immunogenicity in humans could be improved with several strategies [ 41 ]. Given these advantages, influenza DNA vaccines have the potential to provide a broader protection as universal vaccines with the characteristics of easy preparation, simplicity of formulation, high stability and safety by lacking infectious regents [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genome insertion could be controlled with modified DNA sequences and their low immunogenicity in humans could be improved with several strategies [ 41 ]. Given these advantages, influenza DNA vaccines have the potential to provide a broader protection as universal vaccines with the characteristics of easy preparation, simplicity of formulation, high stability and safety by lacking infectious regents [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, Martinon et al demonstrated that administration of mice with a mixture of mRNA encoding flu virus nucleoprotein and liposome induced in vaccinated rodents anti-viral T cell responses [ 30 ]. Based on these data, nucleic acid immunization has received considerable scientific interest because of its significant advantages in comparison to conventional vaccines, i.e., ease of manufacturing, high stability, the capability of modifying genes encoding desired antigens, the ability to target cellular localization of an antigen by adding or removing signal sequences or transmembrane domains, and even the ability to elicit the type of immune response [ 31 , 32 , 33 , 34 ]. However, mRNA vaccine technology was halted for many years due to difficulties in manufacturing, the short half-life of mRNA, and its ability to activate the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In this pilot study, we developed the mRNA counterpart of our MultiTEP-based AV-1959D DNA vaccine using Vernal's proprietary vector for mRNA synthesis (Figure 1A). Specifically, the mRNA encodes the AV-1959 protein, which comprises three copies of the N-terminal region of human Aβ spanning amino acids 1-11, attached to an immunogenic vaccine platform, MultiTEP, consisting of twelve foreign promiscuous T helper (Th) cell epitopes, including one synthetic peptide (PADRE), eight epitopes from Tetanus Toxin (TT) (P2, P21, P23, P30, P32, P7, P17, and P28), two epitopes from HBV surface antigen (HBsAg, aa [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and the nucleocapsid (HBVnc, aa 50-69), respectively, and one epitope from influenza virus matrix protein (MT, aa [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The mRNA synthesis involved the incorporation of modified N1-methylPseudoUridine and capping (CAP1) at the 5 ′ end.…”
Section: Av-1959lr An Mrna-based Vaccine: the Counterpart Of The Av-1...mentioning
confidence: 99%
“…It should also be noted that the DNA vaccine against highly pathogenic influenza A (H5N1) for chicken immunization, developed by Agrilabs, has recently been licensed by the US Department of Agriculture [22]. However, a number of issues related to this platform remain not fully resolved, in particular problems associated with the delivery of a DNA vaccine [11,23,24].…”
Section: Introductionmentioning
confidence: 99%